Energy Efficiency: A New Concern for Application Software Developers. - PINTO, GUSTAVO; CASTOR, FERNANDO (Communications of the ACM, 2017)
The article discusses the relevance of energy efficiency as a consideration for application software development. Topics include research on software energy consumption, the relation of energy consumption to software engineering methodology, and the maintenance of software for energy efficiency in relation to refactoring, reengineering, and visualization.